Components of obstetric violence: A descriptive study on physical abuse, non-consented care and non-confidential care - Okyay, Esra Karataş; Bal, Zeynep; Barut, Sümeyye; Güney, Esra (National Scientific Medical Center, 2022)
Objective: This study aimed at assessing the components of obstetric violence of women in receiving care during labor and postnatal period. Material and methods: This research was designed as a web-based descriptive study. The study was conducted with 556 women who had a vaginal delivery were within the first 6 weeks after delivery. The data of the research were collected between November-December 2021. Results: The mean age of women was 27.33±5.75, and the mean gestational week was 38.96±1.42. It was determined that while 95% of the women who underwent the intervention had a vaginal examination for less than 4 hours, 86.9% of them had no freedom of positioning at birth, and information was not provided to 41.2% of them before shaving, 22.2% of them before the amniotomy, 6.3% of them before oxytocin administration, 7.8% of them before episiotomy administration, 23.6% of them before fundal pressure, and 88.9% of them before vacuum support. It was found that 69.8% of the women did not have a companion during the delivery process, 67.1% of them were not involved in the decisions during the delivery process, and 93.9% of them asked for getting permission and providing information in the interventions during the delivery process. Additionally, the difference between the distributions of exposure to obstetric violence according to some sociodemographic and obstetric characteristics of the women was not statistically significant (p<0.05). Conclusion: According to the result of the study, it was determined that women were subjected to some types of obstetric violence during labor and the delivery process. © 2022, National Scientific Medical Center. All rights reserved.
Keywords: midwifery; non-confidential care; non-consented care; obstetric violence; physical abuse